Eksistensi Kalender Bali dalam Kultur Sosial Masyarakat Multireligius Bali - Fajri Zulia Ramdhani (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2020)
The Balinese calendar is a local Indonesian genius that still exists today. Although identical with Hindu religious rites, the Balinese calendar is also used in the daily activities of the whole community. Because its content consists of information that is not found in the calendar that spread nationally. With regard to the social culture present in this Balinese multireligious society, the Balinese calendar then becomes an interesting discussion. This paper aims to enrich the treasury of the Balinese calendar discourse in the community’s social culture. So this article contains how the history of the Balinese calendar and the contents contained therein. Also, its existence in various sectors is urgent especially in the social culture of a multireligious community. The method used in this study is library research by examining various documents and scientific works, as well as interviews with Muslim community’s leaders in the Klungkung, Bali. This paper describes the conclusion that the Balinese calendar was known at the time of the great tradition-oriented to Hindu religion and culture. The Balinese calendar contains at least some dating systems such as AD, Hijri, Chinese, Balinese Caka, Islamic Java, Tiki, and Pawukon. The Balinese calendar is used in inter-community cultural-social affairs such as determining good days in various fields, knowing market days, understanding holidays that only apply in the Bali area, and so on